In Between Research Cultures – The State of Digital Humanities in Finland - Matres Inés; Oiva Mila; Tolonen Mikko (My University, 2025)
Digital humanities (DH) as a research field has been developing rapidly in Finland during the past few years,
mainly due to increased funding and profiling activities. Although these infrastructural developments have
created (smaller and larger) centres, hubs and clusters related directly or indirectly to digital humanities, the
future of Finnish research in this area depends on how the various scholarly and memory organisations, as
well as individual scholars, succeed in joining forces. The overall argument in this paper is that digital huma-
nities needs to establish its identity and to create a new space among research cultures with varying charac-
teristics tackling a multitude of problems, and that this can only be achieved through national collaboration
and the joint exploitation of the strengths of existing DH hubs. The article sets out a roadmap to this end,
providing a detailed discussion of various developments in digital humanities, and analysing different possi-
bilities in the international context. It is based on a survey conducted in 2016 among Finnish scholars in the
fields of humanities and the social sciences, an analysis of existing infrastructures, and interviews with DH
scholars involved with international top-level DH centres. The focus in the latter part of the article is on the-
se interviews, and on the lessons learned abroad from which the Finnish DH community could benefit. We
conclude with a strong call for collaboration to facilitate the further development of the DH field in Finland
in response to international competition.
Asiasanat: digital humanities; research infrastructures; digital research practices; Finland; data; collaboration;
open science